Hiding in the shadows : the growth of the underground economy - Schneider, Friedrich (Economic issues (International Monetary Fund), 2002)
"A factory worker has a second job driving an unlicensed taxi at night; a plumber fixes a broken water pipe for a client, gets paid in cash but doesn't declare his earnings to the tax collector; a drug dealer brokers a sale with a prospective customer on a street corner. These are all examples of the underground or shadow economy - activities, both legal and illegal, that add up to trillions of dollars a year that take place "off the books," out of the gaze of taxmen and government statisticians. Although crime and shadow economic activities have long been a fact of life - and are now increasing around the world - almost all societies try to control their growth, because of the potentially serious consequences."--Preface